The Development of Subject Specific Pedagogy with SETS Vision to Improve Science Process Skills and Learning Motivation - Prastyo, Erwin (Proceeding International Conference on Science and Engineering, 2020)
The aims of this research are to develop Subject Specific Pedagogy with SETS vision that consist of syllabus, lesson plans, students worksheets, and evaluation sheets that can be applied in teaching learning to develop science process skills and learning science motivation for seventh grade students in Junior High School. The study was a Research and Development (R&D) with students in class VII MTs Darul Ishlah Sukorejo as a subject of study. The research start from September to November 2019. The study began with a literature study and field study to obtain information about the problem faced at school, and followed by planning, drafting and validating product by experts. The result shows that Subject Specific Pedagogy with SETS vision feasible to use in teaching and learning based on the validation result from lecturer, teacher, and student response. The Subject Specific Pedagogy with SETS vision potential for develop the science process skills and learning science motivation of students.